Viper and cobra venom neutralization by alginate coated multicomponent polyvalent antivenom administered by the oral route. - Sourav Bhattacharya; Mousumi Chakraborty; Piyasi Mukhopadhyay; P P Kundu; Roshnara Mishra (Public Library of Science (PLoS), 2014)
BACKGROUND:Snake bite causes greater mortality than most of the other neglected tropical diseases. Snake antivenom, although effective in minimizing mortality in developed countries, is not equally so in developing countries due to its poor availability in remote snake infested areas as, and when, required. An alternative approach in this direction could be taken by making orally deliverable polyvalent antivenom formulation, preferably under a globally integrated strategy, for using it as a first aid during transit time from remote trauma sites to hospitals. METHODOLOGY/PRINCIPAL FINDINGS:To address this problem, multiple components of polyvalent antivenom were entrapped in alginate. Structural analysis, scanning electron microscopy, entrapment efficiency, loading capacity, swelling study, in vitro pH sensitive release, acid digestion, mucoadhesive property and venom neutralization were studied in in vitro and in vivo models. Results showed that alginate retained its mucoadhesive, acid protective and pH sensitive swelling property after entrapping antivenom. After pH dependent release from alginate beads, antivenom (ASVS) significantly neutralized phospholipaseA2 activity, hemolysis, lactate dehydrogenase activity and lethality of venom. In ex vivo mice intestinal preparation, ASVS was absorbed significantly through the intestine and it inhibited venom lethality which indicated that all the components of antivenom required for neutralization of venom lethality were retained despite absorption across the intestinal layer. Results from in vivo studies indicated that orally delivered ASVS can significantly neutralize venom effects, depicted by protection against lethality, decreased hemotoxicity and renal toxicity caused by russell viper venom. CONCLUSIONS/SIGNIFICANCE:Alginate was effective in entrapping all the structural components of ASVS, which on release and intestinal absorption effectively reconstituted the function of antivenom in neutralizing viper and cobra venom. Further research in this direction can strategize to counter such dilemma in snake bite management by promoting control release and oral antivenom rendered as a first aid.